Place Attachment and Zion in Isaiah and Jeremiah - Mylonas, Natalie; Bosworth, David A. 1972- (2025)
Isaiah and Jeremiah reflect an emotional relationship with Jerusalem from preexilic times, through the destruction of the city, exile, and restoration. The connection between place and emotion emerges especially in the personification of Zion as a woman. Love for the city appears in the four main characteristics of attachment relationships: proximity maintenance, safe haven, secure base, separation distress. Zion as mother, daughter, and wife involves its inhabitants in emotional entanglements with place.
Keywords: Zion; Emotion; Place attachment; Space